Brain abscess associated with Mycoplasma faucium – The initial presentation of pulmonary arteriovenous malformation. (2022) - Rothman, Ryan; Saini, Vikram; Min, Zaw; Bhanot, Nitin
Abstract: Brain abscesses represent a pathology with significant morbidity and mortality. An underlying predisposing condition may not be apparent or identifiable in some instances. We present a patient with cerebral abscess who was found to have, previously undiagnosed, pulmonary arteriovenous malformations (PAVMs). PAVMs are rare pulmonary vascular anomalies resulting in intrapulmonary right to left shunt. These have been implicated in the development of brain abscesses. Conventional cultures from the lesion were non-revealing; hence, sample was sent for next-generation sequencing (NGS) which revealed multiple organisms, with predominance of Mycoplasma faucium, a bacterium initially felt to be a commensal of the oropharynx, but recently implicated as a human pathogen. This case, along with other documented associations between brain abscesses and pulmonary AVMs, highlights that brain abscess could be an initial clinical presentation in asymptomatic PAVMs. Additionally, novel testing such as NGS should be utilized in select settings where microbiological diagnosis can be elusive. This will help institute pathogen-directed specific antimicrobial therapy for favorable clinical outcomes.